Significantly improved photocurrent response of ZnS-reduced graphene oxide composites - Sookhakian, M.; Amin, Y.M.; Zakaria, R.; Basirun, Wan Jefrey; Mahmoudian, M.R.; Nasiri-Tabrizi, B.; Baradaran, S.; Azarang, M. (Elsevier, 2015)
ZnS-nanoparticles (NPs) reduced graphene oxide (rGO) composites with a high degree of crystallinity and high dispersity were successfully synthesized via a facile solvothermal method in the gelatin medium, during which the formation of ZnS NPs, reduction of graphene oxide and loading of ZnS NPs into the rGO surface occur simultaneously. Gelatin, as a natural capping agent, plays a significant role in controlling the degree of dispersion and coverage of ZnS NPs. The effect of rGO on the crystalline structure and optical properties of ZnS NPs were determined via X-ray diffraction, UV-visible diffused reflectance spectroscopy and photoluminescence spectroscopy. The ZnS-rGO composites exhibit excellent potential for photocurrent generation compared with pure ZnS NPs under visible light irradiation, provided that efficient photoinduced charge separation and transportation can be achieved at the interface. The maximum photocurrent response was obtained for ZnS-rGO composite with a 3% mass fraction of rGO, which is 2 times that achieved on pure ZnS NPs. (C) 2015 Elsevier B.V. All rights reserved.